2015
DOI: 10.1155/2015/960263
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Self-Management Behaviors in Older Adults with Hypertension

Abstract: The purpose of this study was to develop a prediction model of demographic and sociobehavioral characteristics common among older adults with hypertension (HTN) who engage in self-management behavior. A descriptive, correlational predictive design was used to collect data at 14 faith-based and senior citizen organizations in a major urban northeastern city. Participants ranged in age from 63 to 96 with a mean age of 77 (SD 6.9). A 33-item questionnaire was used to gather data on 15 explanatory and 5 outcome va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…It also be reported that education benefits the understanding about the prevention and controlling of disease, thereby having better self-care [25]. Our finding implies that health professionals should focus more on education about the knowledge of hypertension for those without hypertension to increase their self-management behavior on prevention of hypertension [26].…”
Section: Discussionsupporting
confidence: 55%
“…It also be reported that education benefits the understanding about the prevention and controlling of disease, thereby having better self-care [25]. Our finding implies that health professionals should focus more on education about the knowledge of hypertension for those without hypertension to increase their self-management behavior on prevention of hypertension [26].…”
Section: Discussionsupporting
confidence: 55%
“…Secondly, we included both healthy and unhealthy participants, and stratified the analyses by risk profile. To date, most studies into self-management have involved older adults with a chronic disorder or some other health condition [6][7][8]. Thirdly, the concepts of ability [17], behavior [18], and support [19] were assessed using comprehensive and psychometrically sound measurement instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing self-management may be a relatively low-cost way of improving health outcomes in older adults and in patients with chronic conditions [3]. "Selfmanagement" is a term that is often used in connection with an individual's level of health (which has been shown to be associated with their level of self-management) [5][6][7][8]. However, selfmanagement is also essential for maintaining the well-being of older adults, regardless of their health status.…”
Section: Introductionmentioning
confidence: 99%
“…This is associated with various factors such as age, body weight (obese), lower level of education, an unbalanced dietary pattern, regular drinking and non-comorbidities (Yang et al, 2017). Therefore, behavior management (Douglas and Howard. 2015) and self-efficacy (Sol et al, 2006) are needed for maintaining blood pressure and its factors among the elderly to keep the hypertension problem under control.…”
Section: Introductionmentioning
confidence: 99%